(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Spinal pathologies like cervical spondylosis and lumbar spondylosis have become very much prevalent due to lifestyle and environmental factors. Neck pain and low back pain is the leading cause of years lived with disabilities. Ayurveda always insisted on intervening at the early stage of every disease so that the progress of pathology can be prevented. To counteract these conditions, Ayurveda has put forth six-fold treatment methodologies called Shadupakrama. Rukshana is one among them which can be used as both Bahiparimarjana and Antahparimarjana chikitsa. With Rukshana therapy, the body’s oily, sticky, fatty constituents are dried up and reduced. In this case series, three cases related to spinal pathology, especially cervical and lumbar spondylosis were successfully treated by incorporating the principle of Rukshana. Initially, the condition was visualized as Kaphavruta Vata/Vataanubandha Kapha. Hence the first line of treatment should be Kaphavatahara. Apart from these there is the involvement of Ama in the Samprapthi and considering all these factors internally Rukshana was attained via oral medications and externally by Rukshana upakrama. After the Rukshana therapy patient shows marked improvement, assessments were recorded by comparing the grade of pain, joint tenderness, and range of motion before and after treatment. Notable changes are evidence that the Ayurvedic way of approach to treating spinal disorders is effective and successful. After Rukshana karma, Snigdha bahya karma was adopted along with some internal medications.